Struggles in Leveraging and Commercializing Non-Timber Forest Products for Sustainable Livelihoods: A Study of the Baiga and Gond Tribal Communities in Balaghat District, Madhya Pradesh - Bhattacharya, Ajoy Kumar; Anjali; Upadhyay, Anup Prakash; Kumar, CVRS Vijay (Indian Forester, 2025)
Forests are Non-Timber Forest Products (NTFPs), such as fruits, nuts, medicinal plants, and resins, play a significant role in the livelihoods of forest-dependent communities. This study examines the socioeconomic dynamics and challenges faced by the Baiga and Gond tribes in Madhya Pradesh, India, with a focus on NTFP commercialization. The study was conducted in ten villages within the Bhimlat Block of Balaghat District. The research utilized qualitative methods, including in-depth interviews, focus group discussions, and participatory approaches. A total of 168 respondents, comprising both Baiga and Gond tribes, were surveyed. The findings highlight that 88% of the Baiga population relies heavily on NTFPs. The study reveals that while NTFPs are integral to the local economy, commercialization efforts are impeded by poor market conditions, low pricing, post harvest losses, and access restrictions in protected areas. The regression analysis examining income through NTFPs in relation to gender, education, and age reveals significant disparities and insights. Modern interventions, such as government housing schemes, often fail to align with the cultural needs of the Baiga and Gond tribes, underscoring the need for culturally informed approaches. NGOs and forest departments address these challenges by improving market access, supporting quality maintenance, and providing institutional support. However, a comprehensive strategy is essential, incorporating better market infrastructure, preserving traditional knowledge and integrating gender equity and education. Enhancing NTFP commercialization through these multifaceted interventions will promote socioeconomic resilience and ecological sustainability in forest-dependent communities.